Relationship between Plant Biodiversity and Carbon Stock in Rural Area of Cisadane Watershed - Sunardi Sunardi; Regan Leonardus Kaswanto; Sofyan Sjaf (School of Postgraduate Studies, Diponegoro Univer, 2020)
The main activities in the rural landscape are agriculture, involved natural resources management that compose the function of area as settlement, government services, social services and economy activities. These activities affected the rural landscape that changed plant diversities as well as carbon stock. The aim of this research was to evaluate biodiversity and carbon stock in the rural area of Cisadane Watershed. Two villages were defined on a purposive random sampling, i.e. Sukadamai and Bantarsari. The sampling plots were selected based on main land use type with size for tree was 20 m × 20 m, pole was 10 m x 10 m, sapling was 5 m x 5 m and seedling was 2 m x 2 m; with 3 replications. Similarly, other concentric plots were established. The number of plant species were counted, diameter at breast height (DBH) and plant height were measured. The analysis of carbon stock, plant diversity and the relationship was developed using Microsoft Excel and R 3.6.1 software. The results showed that main land use in Sukadamai and Bantarsari Village consisted of settlement area, farmland, mixed farming and palm oil plantation. In the research area where 106 species from 43 families that classified into 9 horizontal diversity based on function and 5 vertical diversity based on plant height. The values of Shannon-Wiener Diversity Index (H’) ranged 2,78–3,20. Estimated carbon stocks were 1,16–51,40 Mg ha−1 in research areas, respectively. These research concluded there was a negative correlation between species richness and diversity index with carbon stock in the village landscapes.ABSTRACTThe main activities in the rural landscape are agriculture, involved natural resources management that compose the function of area as settlement, government services, social services and economy activities. These activities affected the rural landscape that changed plant diversities as well as carbon stock. The aim of this research was to evaluate biodiversity and carbon stock in the rural area of Cisadane Watershed. Two villages were defined on a purposive random sampling, i.e. Sukadamai and Bantarsari. The sampling plots were selected based on main land use type with size for tree was 20 m × 20 m, pole was 10 m x 10 m, sapling was 5 m x 5 m and seedling was 2 m x 2 m; with 3 replications. Similarly, other concentric plots were established. The number of plant species were counted, diameter at breast height (DBH) and plant height were measured. The analysis of carbon stock, plant diversity and the relationship was developed using Microsoft Excel and R 3.6.1 software. The results showed that main land use in Sukadamai and Bantarsari Village consisted of settlement area, farmland, mixed farming and palm oil plantation. In the research area where 106 species from 43 families that classified into 9 horizontal diversity based on function and 5 vertical diversity based on plant height. The values of Shannon-Wiener Diversity Index (H’) ranged 2,78–3,20. Estimated carbon stocks were 1,16–51,40 Mg ha−1 in research areas, respectively. These research concluded there was a negative correlation between species richness and diversity index with carbon stock in the village landscapes.